Diseminasi Batik Papua melalui Video Dokumenter (Studi Kasus Pada Sentra Batik Phokouw Faa) - Darmawan, Andrie Rizky (Visualita Jurnal Online Desain Komunikasi Visual, 2019)
Papuan batik is batik originating from the Province of Papua, Indonesia. The batik was produced by the Phokouw Faa batik center in Papua Province. The batik center of Phokouw Faa realizes that the batik that he manufactures is not evenly recognized in Papua Province, so that efforts are needed to inform the existence of the Papua batik. The method used in this research is an experiment on the application of elements and principles of visual communication design using non-conventional media (non-print), namely on time-based digital media in the form of documentary videos. Data to design a visual communication about Papuan batik was obtained during a field survey by observing and interviewing. The identities of the Papua province were applied in developing the documentary video. The full results of the research can be seen on the Youtube link as follow https://youtu.be/M5EP0b3jaBs.